Method for batch preparation of calcium-based adsorbent particles with high CO2 adsorbability through wet mixing mechanical modification
By combining wet mixing mechanical modification and extrusion molding methods, calcium-based adsorbent granules with high CO2 adsorption are prepared, which solves the problem of poor CO2 capture performance of existing calcium-based adsorbent granules, and achieves high-efficiency large-scale preparation of calcium-based adsorbent granules, with good industrial application prospects.
Patent Information
- Application Number
- CN202411870889.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-07
AI Technical Summary
The existing calcium-based adsorbent particles have poor performance in CO2 capture performance, and the existing modification methods are complex and costly, making it difficult to achieve industrialized large-scale preparation.
The wet mixed mechanical modification method and the extrusion molding method are combined with the extrusion molding method. By adding support material and water to the calcium-based powder for wet ball milling, mud and extrusion molding, and finally calcining, calcium-based adsorbent granules with high CO2 adsorption are prepared.
The CO2 capture performance of calcium-based adsorbent particles has been significantly improved. The cumulative CO2 adsorption capacity of the fifteenth cycle has increased by 12.14-24.22% compared with ordinary adsorbent particles. It has simple process flow and high production efficiency, and has the prospect of industrial application.
Smart Images

Figure CN119565557A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to CO 2 The field of capture technology, more specifically, relates to a wet mixed mechanical modification batch preparation of high CO 2 Method for adsorbing calcium-based adsorbent particles. Background Art
[0002] CO 2 Large amounts of anthropogenic emissions have intensified the greenhouse effect, which is considered to be one of the main causes of global warming. 2 Human-caused emissions are mainly concentrated in large-scale fossil energy utilization industries such as thermal power generation, steel production, cement production, and transportation. Controlling CO2 emissions in these industries 2 Emissions are of great significance to the realization of carbon peak and carbon neutrality goals. 2 Capture, utilization and storage (CO 2 Capture, Utilization and Sequestration (CCUS) is a technology that can better achieve large-scale CO 2 Key strategies for reducing emissions.
[0003] Carbonation / calcination cycle for CO adsorption based on calcium-based adsorbents 2 Calcium Looping (CaL) technology can be used for post-combustion CO 2 The capture technology mainly uses calcium-based adsorbents (i.e. calcium oxide) to remove CO from the tail gas of existing power station boilers, cement kilns, industrial kilns and other combustion equipment. 2 Capture and reduce the CO in the system 2 Emissions. Calcium-based adsorbents need to be prepared into particles during the application of calcium recycling technology. At present, the granulation methods of calcium-based adsorbents include extrusion molding, spheroidization, encapsulation, extrusion spheronization and casting. Among them, the extrusion method has the highest efficiency in preparing adsorbent particles and is suitable for industrial production applications. However, the particles prepared by the extrusion method have relatively low carbon capture performance due to their overly dense internal structure. Some researchers have achieved the improvement of the carbon capture performance of adsorbent particles through acid modification, high-temperature pre-sintering, steam activation, inert skeleton doping, alkali metal salt modification, sol-gel method, flame synthesis method and other means. However, these modification methods are still in the laboratory research and development stage, with high costs and complex processes. It is difficult to achieve industrial application in a short period of time and realize the large-scale preparation of high-performance calcium-based adsorbent particles.
[0004] Therefore, in order to solve the above problems, a wet mixing mechanical modification method for batch preparation of high CO 2The method of producing adsorbent calcium-based adsorbent particles is intended to achieve mass production of high-performance calcium-based adsorbent particles to meet the carbon capture needs of industries such as thermal power generation, steel production, cement production, and transportation. Summary of the invention
[0005] The present invention aims to solve two main technical problems. One is to improve the carbon capture performance of calcium-based adsorbent particles. The extrusion molding method for preparing calcium-based adsorbent particles has the greatest potential for industrial application due to its high production efficiency. However, the particles prepared by the extrusion molding method have an overly dense internal structure, which results in CO 2 It is difficult to diffuse into the interior of the particles, resulting in low carbon capture performance of the adsorbent particles; secondly, to achieve industrial mass production of high-performance calcium-based adsorbent particles. Existing methods such as acid modification, high-temperature pre-sintering, steam activation, inert skeleton doping, alkali metal salt modification, sol-gel method, and flame synthesis method can all improve the carbon capture performance of adsorbent particles, but these methods are complex and costly and are difficult to achieve industrial application at the current stage. In response to the above two problems, the present invention proposes a wet mixing mechanical modification method for batch preparation of high CO 2 The invention discloses a method for preparing adsorbent calcium-based adsorbent particles. The method is based on an extrusion molding method and combined with a wet mixing mechanical modification method. The method can improve the carbon capture performance of the calcium-based adsorbent particles. At the same time, the method has a simple process flow, high production efficiency, and has prospects for industrial application.
[0006] According to a first aspect of the present invention, there is provided a method for preparing calcium-based adsorbent particles in batches by wet mixing and mechanical modification, comprising the following steps:
[0007] (1) adding a supporting material with aluminum oxide as the main component to a calcium-based powder, wherein the calcium-based powder is slaked lime or limestone; then adding water, and then wet ball milling to obtain a block-shaped mud material;
[0008] (2) adding the block-shaped mud material obtained in step (1) into a mud refiner for mud refining to obtain a homogeneous mass-shaped mud material;
[0009] (3) adding the agglomerated mud obtained in step (2) into an extruder to extrude into strips, cutting into particles, and then drying;
[0010] (4) calcining the dried particles obtained in step (3) to obtain calcium-based adsorbent particles.
[0011] Preferably, the mass ratio of the calcium-based powder to the support material is 9:(1-3).
[0012] Preferably, in step (1), the ratio of the mass of water to the sum of the mass of the calcium-based powder and the support material is 10:(4-25).
[0013] Preferably, the support material is pseudo-boehmite, cordierite, bauxite, kaolin or bentonite.
[0014] Preferably, the rotation speed of the ball mill is 150-250 r / min, the ball-to-material ratio is 5:(1-25), and the ball milling time is 0.5-2 h.
[0015] Preferably, the calcination temperature is 700-900°C.
[0016] Preferably, the drying temperature is 80-110°C.
[0017] Preferably, in step (3), the particles have a diameter of 5-6 mm and a length of 5-6 mm.
[0018] Preferably, the ball mill used in the ball milling is a planetary ball mill.
[0019] According to another aspect of the present invention, provided are prepared calcium-based adsorbent particles.
[0020] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0021] (1) The wet mixing mechanical modification method of the present invention can produce multiple promoting effects on the material: first, the wet mixing mechanical modification method uses water as the dispersed phase to make the powder mixing more uniform; second, the large-particle powder in the powder is broken under the action of mechanical force to form a smaller size, thereby increasing the specific surface area and pore volume of the powder; third, due to the presence of water, excessive grinding of the powder by mechanical force can be avoided, and the occurrence of cold welding and agglomeration can be avoided; these three effects can all improve the carbon capture performance of the adsorbent.
[0022] (2) The extrusion molding method mainly includes three steps: powder mixing, agglomeration, and extrusion molding. The wet mixing mechanical modification method uses mechanical equipment such as a ball mill to mechanically grind the powder added with water as the dispersed phase. On the one hand, it plays a modification role and improves the carbon capture capacity of the adsorbent. On the other hand, it can also play the role of powder mixing and agglomeration, and the powder mixing is more uniform. Using wet mixing mechanical modification to replace the two steps of powder mixing and agglomeration in the extrusion molding method can not only improve the uniformity of powder mixing, but also will not make the process cumbersome, with high production efficiency and great prospects for industrial application.
[0023] (3) The method proposed in the present invention combines the wet mixing mechanical modified extrusion molding method. Compared with the ordinary extrusion molding method, the calcium-based adsorbent particles produced by the method have better carbon capture performance and cycle stability. The high-performance calcium-based adsorbent particles have accumulated CO2 in fifteen cycles. 2The adsorption capacity can be increased by 12.14-24.22% compared with ordinary calcium-based adsorbent particles.
[0024] (4) The present invention combines the extrusion molding method with wet mixing mechanical modification, and still retains the simple steps of the extrusion molding method. It only replaces the original powder mixing and material agglomeration process with a wet mixing mechanical modification process, and does not overly complicate the process flow. Compared with the spheroidization method, the cladding method, the extrusion spheronization method and the casting method, the wet mixing mechanical modification process has the highest production efficiency and the most promising industrial application prospects. Third, compared with acid modification, high-temperature pre-sintering, steam activation, inert skeleton doping, alkali metal salt modification, sol-gel method, flame synthesis method and other modification methods, the wet mixing mechanical modification process is simple to operate, has high output, and takes less time, and can be perfectly coupled with the extrusion molding method, and has a strong basis for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the process flow of the present invention.
[0026] Figure 2 This is a diagram of the particle preparation process of the present invention.
[0027] Figure 3 The initial CO of the calcium-based adsorbent particles of Examples 1-3 and Comparative Example 1 2 capture performance.
[0028] Figure 4 The calcium-based adsorbent particles of Examples 1-3 and Comparative Example 1 were 15 cycles of CO 2 Capture performance results, where (a) is the adsorption capacity per cycle and (b) is the cumulative adsorption capacity after fifteen cycles.
[0029] Figure 5 The SEM characterizations of Example 2 and Control Example 1, wherein (a) is the SEM characterization of the sample particles of Example 2, and (b) is the SEM characterization of the sample particles of Control Example 1.
[0030] Figure 6 This is the PSD test of Example 2 and Comparative Example 1. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0032] The present invention proposes a method for preparing high CO in batches by wet mixing mechanical modification 2The method of preparing calcium-based adsorbent particles with good adsorption performance. The detailed process flow of the method is as follows:
[0033] (1) Weigh a certain amount of calcium hydroxide powder (not limited to calcium hydroxide, it can also be limestone calcium-based powder, calcium hydroxide is preferred here), add a certain amount of pseudo-boehmite (its main components are aluminum oxide and silicon oxide, in addition to pseudo-boehmite, cordierite, bauxite, kaolin, bentonite, high-alumina cement and other various supports can also be added, pseudo-boehmite is preferred here).
[0034] (2) In this scheme, a ball mill is selected as a wet mixing mechanical modification device, and the weighed calcium hydroxide and pseudo-boehmite powders are placed in a grinding jar, and a certain amount of ball milling beads and a certain amount of water are added thereto. The grinding jar is then fixed in a planetary ball mill, and wet mixing mechanical modification is performed at a speed of 200r / min. After the wet mixing mechanical modification is completed, a material screening device is used to screen the ball milling beads and the block mud material to obtain the modified block mud material. (The present invention does not specifically limit the amount of water added, the ball milling time and the ball milling speed in the wet mixing mechanical modification method, as long as the powder can be fully mixed and agglomerated. The present invention preferably has a water-to-powder ratio (mass ratio) in the range of 1:2.5 to 2.5:1; the preferred ball milling time is 0.5-2h; and the preferred ball milling speed is 200r / min.)
[0035] (3) The obtained block mud is then placed in a twin-screw mud refiner, and the mud is repeatedly refined and stirred to form a homogeneous lump mud.
[0036] (4) The homogeneous mass of mud is extruded into strips by a hydraulic extruder, and cut by an automatic cutting machine. The cut particles are placed in a drying oven and dried at 80-110° C. to obtain particles with a diameter of 5-6 mm and a length of 5-6 mm.
[0037] (5) placing the particles in a high-temperature atmosphere furnace for high-temperature calcination, wherein the temperature of the atmosphere furnace ranges from 700 to 900° C., and dry air is continuously introduced into the furnace during the calcination process. After the calcination is completed, calcium-based adsorbent particles can be obtained.
[0038] The process flow diagram of the present invention is as follows Figure 1 The particle preparation process is shown in Figure 2 shown.
[0039] The present invention couples the wet mixing mechanical modification method with the extrusion molding method to achieve industrial batch preparation of high-performance calcium-based adsorbent particles. First, the wet mixing mechanical modification method makes the powder mixing more uniform by continuous grinding; second, during the continuous grinding process, the particle size of the powder becomes smaller, and its specific surface area and pore volume are increased, making the microscopic pore structure of the adsorbent particles richer, which is conducive to the diffusion and adsorption of carbon dioxide, and significantly improving the CO2 absorption of the adsorbent particles.2 Capture performance; 3. Due to the addition of water during the grinding process, on the one hand, as a dispersed phase, it is more helpful to promote the uniform mixing of powders, and on the other hand, the addition of water can avoid cold welding and agglomeration of powders caused by excessive grinding; 4. The wet mixing mechanical modification method can replace the two steps of powder mixing and material agglomeration in the extrusion molding method, without adding unnecessary steps. In the actual production process of adsorbent particles, the process flow is not complicated; 5. The wet mixing mechanical modification method can be realized by relying on mechanical grinding equipment and material screening equipment, and mechanical grinding equipment and material screening equipment have long been applied in factories. Therefore, the high-performance calcium-based adsorbent particle preparation method coupled with the wet mixing mechanical modification method and the extrusion molding method has strong industrial application potential and prospects.
[0040] In the following specific examples, slaked lime is a commercially available product, the main component of which is Ca(OH) 2 , with a mass percentage of 90-95%; pseudo-boehmite is a commercially available product, the main components of which are aluminum oxide and silicon oxide. A fixed bed reactor was used to carry out CO 2 Capture performance test; use SEM, BET and PSD to conduct microscopic analysis and comparison of samples.
[0041] Fixed bed reactor sample CO 2 Capture performance test: 10g of calcium-based adsorbent sample was loaded into a vertical fixed-bed reactor, and simulated flue gas was introduced for performance evaluation. The test operating conditions of the fixed-bed reactor were: simulated flue gas flow rate of 1L / min, composition of 15% CO 2 and 85% N 2 , adsorption temperature was 650℃, and reaction time was 120min. 2 Adsorption capacity was measured for fifteen cycles.
[0042] CO of calcium-based adsorbent samples 2 Capture performance of CO by calcium-based adsorbent samples 2 The adsorption capacity and the cumulative adsorption capacity of fifteen cycles are defined by the following formula:
[0043]
[0044] In the formula: N is the number of cycles; C N is the CO of the calcium-based adsorbent sample in the Nth cycle 2 Adsorption capacity, in gCO 2 / g adsorbent, m car,N is the mass of the calcium-based adsorbent sample after the Nth cycle of carbonation, m cal,N is the mass of the calcium-based adsorbent sample after the Nth cycle of calcination; L 15is the cumulative adsorption capacity of the calcium-based adsorbent sample for fifteen cycles, in gCO 2 / g adsorbent.
[0045] The following are specific examples and comparative examples.
[0046] Example 1
[0047] The preparation process of the present invention is as follows Figure 1 The particle preparation process is shown in Figure 2 211.4g slaked lime powder and 40g pseudo-boehmite were put into a zirconia grinding jar, and 100g zirconia ball milling beads were added, followed by water, ensuring that the mass ratio of water to powder sample was 1:2.5, and then the ball milling jar was sealed and fixed on a planetary ball mill, and ball milled for 1h at a speed of 200r / min. After the ball milling was completed, the ball milling beads and the block mud were screened using a material screening device to obtain a uniform mixture of calcium hydroxide and pseudo-boehmite.
[0048] The mixture is then put into a twin-screw mud refiner, where it is repeatedly refined and stirred to eventually form a fine and homogeneous mud material.
[0049] The lump mud is taken out and then put into a fully automatic hydraulic extruder, the lump mud is extruded into strips, and cut with an automatic cutting machine, the cut particles are put into a drying oven, and dried at 80-110°C to obtain particles with a diameter of 5-6mm and a length of 5-6mm.
[0050] The particles are transferred to a high-temperature atmosphere furnace and calcined at high temperature under high-flow dry air purge conditions, wherein the atmosphere furnace temperature range is 850°C, the air flow rate is 10L / min, and the calcination time is 120min. After calcination, high-performance calcium-based adsorbent particles can be obtained.
[0051] The high-performance calcium-based adsorbent particle sample prepared by the method described in Example 1 was subjected to CO 2 Capture performance test, experimental test conditions and operating conditions are as above, the initial CO of the sample in Example 1 is measured 2 The adsorption capacity is 0.515 gCO 2 / g adsorbent.
[0052] Example 2
[0053] The preparation process of the present invention is as follows Figure 1 The particle preparation process is shown in Figure 2211.4g slaked lime powder and 40g pseudo-boehmite were put into a zirconia grinding jar, and 100g zirconia ball milling beads were added, followed by water added thereto to ensure that the mass ratio of water to powder sample was 1:1, and then the ball milling jar was sealed and fixed on a planetary ball mill, and ball milled for 1h at a speed of 200r / min. After the ball milling was completed, the ball milling beads and the blocky mud were screened using a material screening device to obtain a uniform mixture of calcium hydroxide and pseudo-boehmite.
[0054] The mixture is then put into a twin-screw mud refiner, where it is repeatedly refined and stirred to eventually form a fine and homogeneous mud material.
[0055] The lump mud is taken out and then put into a fully automatic hydraulic extruder, the lump mud is extruded into strips, and cut with an automatic cutting machine, the cut particles are put into a drying oven, and dried at 80-110°C to obtain particles with a diameter of 5-6mm and a length of 5-6mm.
[0056] The particles are transferred to a high-temperature atmosphere furnace and calcined at high temperature under high-flow dry air purge conditions, wherein the atmosphere furnace temperature range is 850°C, the air flow rate is 10L / min, and the calcination time is 120min. After calcination, high-performance calcium-based adsorbent particles can be obtained.
[0057] The high-performance calcium-based adsorbent particle sample prepared by the method described in Example 2 was subjected to CO 2 Capture performance test, experimental test conditions and operating conditions are as above, measured Example 2 sample CO 2 The adsorption capacity is 0.544 gCO 2 / g adsorbent.
[0058] Example 3
[0059] The preparation process of the present invention is as follows Figure 1 The particle preparation process is shown in Figure 2 211.4g slaked lime powder and 40g pseudo-boehmite were put into a zirconia grinding jar, and 100g zirconia ball milling beads were added, followed by water, ensuring that the mass ratio of water to powder sample was 2.5:1, and then the ball milling jar was sealed and fixed on a planetary ball mill, and ball milled for 1h at a speed of 200r / min. After the ball milling was completed, the ball milling beads and the block mud were screened using a material screening device to obtain a uniform mixture of calcium hydroxide and pseudo-boehmite.
[0060] The mixture is then put into a twin-screw mud refiner, where it is repeatedly refined and stirred to eventually form a fine and homogeneous mud material.
[0061] The blocky mud material is taken out and then put into a fully automatic hydraulic extruder, the lumpy mud material is extruded into strips, and cut using an automatic cutting machine, the cut particles are put into a drying oven, and dried at 80-110°C to obtain particles with a diameter of 5-6mm and a length of 5-6mm.
[0062] The particles are transferred to a high-temperature atmosphere furnace and calcined at high temperature under high-flow dry air purge conditions, wherein the atmosphere furnace temperature range is 850°C, the air flow rate is 10L / min, and the calcination time is 120min. After calcination, high-performance calcium-based adsorbent particles can be obtained.
[0063] The high performance calcium-based adsorbent particle sample prepared by the method described in Example 3 was subjected to CO 2 Capture performance test, experimental test conditions and operating conditions are as above, measured Example 3 sample CO 2 The adsorption capacity is 0.526 gCO 2 / g adsorbent.
[0064] Comparative Example 1
[0065] 211.4 g of slaked lime powder and 40 g of pseudo-boehmite were mixed with a V-type dry powder mixer for 1 h to obtain a uniform mixture of calcium hydroxide and pseudo-boehmite powder.
[0066] Then put the powder mixture into a fully automatic mixing machine, add a certain amount of water, repeatedly refine and stir the mud, and finally form a fine and homogeneous lump mud.
[0067] The lump mud is taken out and then put into a fully automatic hydraulic extruder, the lump mud is extruded into strips, and cut with an automatic cutting machine, the cut particles are put into a drying oven, and dried at 80-110°C to obtain particles with a diameter of 5-6mm and a length of 5-6mm.
[0068] The particles are transferred to a high-temperature atmosphere furnace and calcined at high temperature under a large flow rate of dry air purge conditions, wherein the atmosphere furnace temperature range is 850°C, the air flow rate is 10L / min, and the calcination time is 120min. After the calcination is completed, the calcium-based adsorbent particles can be obtained.
[0069] The calcium-based adsorbent particle sample prepared by the method described in this comparative example 1 was subjected to CO 2 Capture performance test, experimental test conditions and operating conditions are as above, the CO of control example 1 sample is measured 2 The adsorption capacity is 0.512gCO 2 / g adsorbent.
[0070] Figure 3The initial CO2 removal rate of the calcium-based adsorbent particles prepared in Examples 1-3 and Comparative Example 1 in a fixed bed reactor was 2 Capture performance test results. Comparative Example 1 is a calcium-based adsorbent particle prepared by a common mixing method. Its initial CO 2 The capture performance is 0.512gCO 2 / g adsorbent, while the calcium-based adsorbent particles of Examples 1-3 prepared by wet mixing mechanical modification have the best initial CO 2 The capture performance is 0.544gCO 2 / g adsorbent.
[0071] Figure 4 Table 1 shows the 15-cycle CO of the calcium-based adsorbent particles prepared in Examples 1-3 and Comparative Example 1. 2 Capture performance results. The calcium-based adsorbent particles of control example 1 prepared by ordinary mixing method have a 15-cycle CO 2 The cumulative adsorption capacity is 5.478 gCO 2 / g adsorbent, which is lower than the calcium-based adsorbent particles of Examples 1-3 prepared by wet mixing mechanical modification. Among them, the modified adsorbent particles prepared in Example 2, i.e., the water-powder ratio of 1:1, have the best adsorption performance. 2 The cumulative adsorption capacity is 6.805gCO 2 / g adsorbent, the performance decay rate is 29.2%. Therefore, the wet mixing mechanical modification method is coupled with the extrusion molding method, and the prepared calcium-based adsorbent particles have higher adsorption performance and better adsorbent cycle stability. In addition, the method has simple operation steps, large output and short time. Using this method, 250g of high-performance calcium-based adsorbent particles can be produced in the laboratory within three hours, and 0.75kg of high-performance calcium-based adsorbent particles can be produced on a laboratory scale every day. Therefore, this method has great prospects for industrial application.
[0072] Table 1 Examples 1-3 and Comparative Example 1 Calcium-based adsorbent particles Ten cycles of CO 2 Capture performance results
[0073]
[0074]
[0075] At the same time, SEM, BET, and PSD methods were used to characterize and analyze the high-performance calcium-based adsorbent particles of the embodiment and the ordinary calcium-based adsorbent particles of the comparative example 1 at the microscopic level. Figure 5 , Figure 6The results show that the high-performance calcium-based adsorbent particles of Example 2 prepared by the wet mixing mechanical modification method have a smaller particle size, a larger specific surface area and a larger total pore volume, and a more developed pore structure, which is more conducive to CO 2 The diffusion of molecules inside it, so its adsorbent particles CO 2 The capture performance and adsorbent cycle stability are better.
[0076] Table 2 BET test results
[0077] <![CDATA[Specific surface area / m 2 g -1 > <![CDATA[Total pore volume / cm 3 g -1 > Example 1 11.17 0.29 Example 2 14.14 0.34 Example 3 9.34 0.30 Comparative Example 1 5.97 0.24
[0078] The present invention proposes a method for preparing high CO in batches by wet mixing mechanical modification 2 The method proposed by the present invention couples wet mixing mechanical modification with extrusion molding. Compared with the existing acid modification, high temperature pre-sintering, steam activation, inert skeleton doping, alkali metal salt modification, sol-gel method, flame synthesis method and other methods, the process flow is simple to operate, with low energy consumption, high efficiency and large output. The kilogram-level preparation can be achieved in the laboratory. At the same time, the calcium-based adsorbent particles prepared by this method have a cumulative CO of 10.33% in fifteen cycles. 2 The adsorption capacity is increased by 12.14-24.22% compared to ordinary adsorbent particles, and it has good cycle stability, and has great prospects for industrial application. It can provide strong support for carbon capture needs in industries such as thermal power generation, steel production, cement production, and transportation.
[0079] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing calcium-based adsorbent particles in batches by wet mixing and mechanical modification, characterized in that: The following steps are involved: (1) adding a supporting material with aluminum oxide as the main component to a calcium-based powder, wherein the calcium-based powder is slaked lime or limestone; then adding water, and then wet ball milling to obtain a block-shaped mud material; (2) adding the block-shaped mud material obtained in step (1) into a mud refiner for mud refining to obtain a homogeneous mass-shaped mud material; (3) adding the agglomerated mud obtained in step (2) into an extruder to extrude into strips, cutting into particles, and then drying; (4) calcining the dried particles obtained in step (3) to obtain calcium-based adsorbent particles.
2. The method for preparing calcium-based adsorbent particles in batches by wet mixing and mechanical modification according to claim 1, characterized in that: The mass ratio of the calcium-based powder to the support material is 9:(1-3).
3. The method for preparing calcium-based adsorbent particles in batches by wet mixing and mechanical modification according to claim 1, characterized in that: In step (1), the ratio of the mass of water to the sum of the mass of the calcium-based powder and the support material is 10:(4-25).
4. The method for preparing calcium-based adsorbent particles in batches by wet mixing mechanical modification according to any one of claims 1 to 3, characterized in that: The support material is pseudo-boehmite, cordierite, bauxite, kaolin or bentonite.
5. The method for preparing calcium-based adsorbent particles in batches by wet mixing and mechanical modification according to claim 1, characterized in that: The rotation speed of the ball mill is 150-250 r / min, the ball-to-material ratio is 5:(1-25), and the ball milling time is 0.5-2 h.
6. The method for preparing calcium-based adsorbent particles in batches by wet mixing and mechanical modification according to claim 1, characterized in that: The calcination temperature is 700-900°C.
7. The method for preparing calcium-based adsorbent particles in batches by wet mixing and mechanical modification according to claim 1, characterized in that: The drying temperature is 80-110°C.
8. The method for preparing calcium-based adsorbent particles in batches by wet mixing and mechanical modification according to claim 1, characterized in that: In step (3), the diameter of the particles is 5-6 mm and the length is 5-6 mm.
9. The method for preparing calcium-based adsorbent particles in batches by wet mixing and mechanical modification according to claim 1, characterized in that: The ball mill used in the ball milling is a planetary ball mill.
10. Calcium-based adsorbent particles prepared according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing wear-resistant nano calcium oxide-based carbon dioxide reaction adsorbent
CN101961638A
Preparation method for calcium-based CO2 sorbent
CN102784630A
Batch production method of doped modified calcium-based CO2 adsorbent spheres
CN112275251A
Calcium-based adsorbent as well as preparation method and application thereof
CN118002067A
highly attrition resistant and dry regenerablesorbents for carbon dioxide capture
KR1020060079589A
Cited By
Industrial batch production method of calcium-based adsorbent particles with high CO2 adsorbability
CN119633741A
Silicon-calcium-based porous material, preparation method thereof and application of silicon-calcium-based porous material as asphalt fume fixing agent
CN120679475A